2021
DOI: 10.3390/jcm10091892
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Media for Preconception Information and Pregnancy Planning among Young Women

Abstract: Young women of reproductive age (18–25 years) often seek and engage with health-related information via social media. However, the extent to which this population group seek preconception and pregnancy-related information has not been explored. Therefore, this study aimed to: (1) examine the proportion, type, and frequency of social media use to seek general health, preconception, and pregnancy-related information or advice among young women; and (2) explore the relationship between age, education status, rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…As can be seen in Table 1 , all included articles were from 2018 and beyond, and four were from 2021. Of the eight selected studies, five were conducted in low- to middle-income countries (Ethiopia, Indonesia, India, and Nigeria) [ 13 , 15 , 17 - 19 ], and three were from high-income countries (the United States, Japan, and Australia) [ 12 , 14 , 16 ]. These findings indicated the increased interest in PCC research following a better understanding of PCC’s importance for women’s and children’s health across the globe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As can be seen in Table 1 , all included articles were from 2018 and beyond, and four were from 2021. Of the eight selected studies, five were conducted in low- to middle-income countries (Ethiopia, Indonesia, India, and Nigeria) [ 13 , 15 , 17 - 19 ], and three were from high-income countries (the United States, Japan, and Australia) [ 12 , 14 , 16 ]. These findings indicated the increased interest in PCC research following a better understanding of PCC’s importance for women’s and children’s health across the globe.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, research in the United States, as a high-income country, reported that half of the young women had basic PCC knowledge, including treatment goals, the urgency of care, folic acid supplementation, genetic counseling, iron supplementation, and family planning [ 12 ]. Meanwhile, an Australian study stated that the adolescents understood well the general health information related to PCC and pregnancy planning [ 16 ]. Last, a study in Japan indicated that the female respondents had broader knowledge about PCC, as the study also mentioned cancer screening, infertility, and rubella prevention [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of digital health such as pregnancy apps, websites, social media, and online communities continue to be highly prevalent during pregnancy [35,[39][40][41], and our ndings suggest that the reliance on these digital media has increased due to the pandemic. While our participants primarily used pregnancy apps to access pregnancy-related information and receive updates about their baby's development -which is consistent with previous cross-sectional studies [35,42] -many also expressed their desire for apps to also provide information about the changes occurring to their own bodies.…”
Section: Discussionmentioning
confidence: 99%
“… 35 Using technologies such as social media and health apps that target those in their reproductive years may be one way to increase awareness of preconception health and encourage conversations with those who provide preconception counselling. 36 In Australia there are limited comprehensive preconception care services that are hospital based, therefore primary healthcare, including preconception care, is delivered by GPs. A study by Kizirian et al 22 found that 50% of GPs were aware of current preconception care guidelines and most do not recognise overweight to be a significant preconception issue.…”
Section: Discussionmentioning
confidence: 99%